2020
DOI: 10.1029/2019jb018558
|View full text |Cite
|
Sign up to set email alerts
|

Induced Seismicity in the Delaware Basin, Texas

Abstract: The seismicity rate in the Delaware Basin, located in western Texas and southeastern New Mexico, has increased by orders of magnitude within the past~5 years. While no seismicity was reported in the southern Delaware Basin during 1980-2014, 37 earthquakes with M > 3 occurred in this area during 2015-2018. We generated an improved catalog of~37,000 earthquakes in this region during 2009-2018 by applying multistation template matching at both regional and local stations using all earthquakes in the Advanced Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 45 publications
(79 reference statements)
4
75
0
Order By: Relevance
“…(c) Time series of earthquakes (circles) and times of HF stimulations (bars) that are shown in (b). Figure modified from Skoumal et al (2020).…”
Section: Summary Of Documented Casesmentioning
confidence: 99%
See 4 more Smart Citations
“…(c) Time series of earthquakes (circles) and times of HF stimulations (bars) that are shown in (b). Figure modified from Skoumal et al (2020).…”
Section: Summary Of Documented Casesmentioning
confidence: 99%
“…No earthquakes greater than 3.0 M had been detected in this area prior to 2015; during 2015–2020, more than 67 earthquakes ( M > 3) occurred, with the largest event being a 5.0 Mw . The majority of the earthquakes have been suggested to be induced by wastewater disposal, with ~5% of seismicity (of 1,850 earthquakes) induced by HF (Skoumal et al, 2020), although another study has suggested HF as a primary factor for inducing many of these events (Lomax & Savvaidis, 2019). This discrepancy highlights potential difficulties of spatiotemporal association to HF stimulation, especially in areas with ongoing earthquakes.…”
Section: Summary Of Documented Casesmentioning
confidence: 99%
See 3 more Smart Citations